The effects of add-on self-care education on quality of life and fatigue in gastrointestinal cancer patients undergoing chemotherapy - Jun Xie; Tingli Zhu; Qun Lu; Xiaomin Xu; Yinghua Cai; Zhenghong Xu (BMC, 2020)
Abstract Background Gastrointestinal cancer is one of the most common malignancies and imposes heavy burdens on both individual health and social economy. We sought to survey the effect of a self-care education program on quality of life and fatigue in gastrointestinal cancer patients who received chemotherapy. Methods Ninety-one eligible gastrointestinal cancer patients were enrolled in this study and 86 valid samples were analyzed. Data were acquired with a demographics questionnaire, endpoint multidimensional questionnaire and the European Organization for Research and Treatment of Cancer (EORTC) quality of life questionnaire QLQ-C30. The collected data were analyzed using SPSS software. Results The self-care education intervention significantly improved the quality of life with respect to emotional function (p = 0.018), role function (p = 0.041), cognitive function (p = 0.038) and alleviated side effects such as nausea/vomiting (p = 0.028) and fatigue (p = 0.029). Further analysis demonstrated that the self-care education benefited total fatigue, affective fatigue and cognitive fatigue in gastrointestinal cancer patients regardless of baseline depression. Conclusion Our results suggested the beneficial effects of the self-care education in both quality of life and anti-fatigue in gastrointestinal cancer patients under chemotherapy. The self-care education could be considered as a complementary approach during combination chemotherapy in gastrointestinal cancer patients.